Murder inside the Beltway : a Capital crimes novel - Truman, Margaret, 1924-2008 (Truman, Margaret, 1924-2008. Capital crimes series., 2008)
On a bright Saturday afternoon on the Washington Mall, the daughter of presidential candidate Robert Colgate's closest friend is kidnapped. The abduction rocks the nation's capital, but no one is prepared for the bombshell about to hit the city, an explosive development that erupts when Detectives Hall and Jackson uncover a shocking connection between the kidnapping and the murder of a Washington, D.C. call girl--and a killer whom no one will see coming.